Andante for the piano forte ... op. 35 [i.e. WoO 57] / composed by Louis van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Cramer, Beale & Co.; London; United Kingdom, 2022)
Edition of the "Andante favori" for piano in F major, WoO 57, published as "op. 35" and "No. 35" in the series "Beethoven's Works edited by J. Moscheles, complete edition" by Cramer, Beale & Co. (201 Regent Street & 67 Conduit Street) in London between 1844-1861 and bound in as part of vol. III of "Beethoven's Sonatas for the Piano edited by I. Moscheles;" reprint of the edition published by Cramer, Addison, & Beale in 1838/1839. At foot of title page: "NB In this edition, the utmost care has been taken to mark by Maelzel's metronome the author's time of each movement."